Accurate detection of the edges of a room in a photograph - Low, Antheberther Hui Si (Nanyang Technological University, 2020)
The objective of this project is to develop a program to extract the structural edges of a room from a 2-Dimensional (2-D)photograph. However, this was faced with initial complicationsas there is noise in everyphotograph. Therefore, we need to first address the core problem of edge detection, followed by the noises that comes with the photograph. The methodologyemployed is broken down into 4 main phases:pre-processing, finding the corners and everyline in the photograph, calculatingthe distance between everycorner point and the linesas well as the distance between the starting and ending points,and lastly displayingthe geometry structures.The program istested on an imageand the results show that most of the structural lines and corners were obtained. Theproblems andobstacles encountered were noises in the image, threshold used and methodology that was used previously.The future work includes improvisation or implementing more condition to the existing ones, smoothen the image for noise reduction and versatility of the program.